2021
DOI: 10.1038/s41598-020-79845-3
|View full text |Cite
|
Sign up to set email alerts
|

Contralesional functional network reorganization of the insular cortex in diffuse low-grade glioma patients

Abstract: Diffuse low-grade gliomas (DLGGs) growing on the insular lobe induce contralesional hemispheric insular lobe compensation of damaged functioning by increasing cortical volumes. However, it remains unclear how functional networks are altered in patients with insular lobe DLGGs during functional compensation. Thirty-five patients with insular DLGGs were classified into the left (insL, n = 16) and right groups (insR, n = 19), and 33 healthy subjects were included in the control group. Resting state functional mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Changes in language network connectivity in non-opercular regions have also been observed. For instance, using resting state fMRI, Fang et al (2021) found networks alterations involving the contralateral insular cortex in patients with low-grade glioma.…”
Section: Local and Cross-regional Adaptations After Injurymentioning
confidence: 99%
“…Changes in language network connectivity in non-opercular regions have also been observed. For instance, using resting state fMRI, Fang et al (2021) found networks alterations involving the contralateral insular cortex in patients with low-grade glioma.…”
Section: Local and Cross-regional Adaptations After Injurymentioning
confidence: 99%
“…The dorsal attention network (DAN) appears to be affected by significant alterations, too; higher FC in frontal and occipital regions and lower in the subcallosum and the anterior cingulate cortex were found independently of the tumor characteristics and mutation status [32]. Another interesting aspect is the specific case of insular diffused low-grade gliomas: independently of the side of the tumor, the contralateral insula shows increased FC, especially towards the visual and sensorimotor networks [49], and higher communication efficiency [50] compared to HCs.…”
Section: Other Functional Networkmentioning
confidence: 99%
“…Being able to assess FC properties in more homogeneous groups of patients will improve the power of the rs-fMRI analysis to determine specific alterations associated with different characteristics of the tumors. [22][23][24][25][26][27][28][29][30]32,33,35,[38][39][40][43][44][45][46][47][49][50][51][52][53][54][55][56], grouped by field of application and reported in order of citation. This information was not available for the other 7 studies [31,34,36,37,41,42,48].…”
Section: Other Functional Networkmentioning
confidence: 99%
See 2 more Smart Citations